Indebtedness among young Muslims in Malaysia: review of the extant literature - Md. Shariff, Anita; Ariffin, Muhammad Irwan; Mohammed, Mustafa Omar (2018)
Evidences show rising trend of household debt especially among young Muslims in Malaysia. The literature has cited several reasons for this which covers macroeconomic, socioeconomic, cultural, psychological and demographic factors. Among all determinants, materialism and religiosity deficit seem to be the least researched factors. Studies argue that the chase for growth and higher living standard has invariably breed materialism in the society which in turn leads to indebtedness. At the same time, young Muslims are struggling to preserve their Islamic religiosity, which discourage indebtedness. Both materialism and Islamic religiosity have opposite impacts on debt. The role of Islamic banking in extending credit to Muslims is another dimension to be considered. On one hand, it claims to pursue a religious objective and on the other hand it offers debt-based products that encourage indebtedness. While Islam discourages indebtedness, more Muslims choose to borrow from Islamic banking for religious reason. There is dearth of literature that has critically examined these three issues: materialism, religiosity deficit and Islamic banking in relation to indebtedness. The present paper adopts a literature survey method to critically review the related works on factors that influence household debt behavior, focusing on these three issues. The paper expects to provide a new direction in the study of indebtedness among young Muslim households in Malaysia.